Body-Specific Attention to the Hands and Feet in Healthy Adults - Aizu, Naoki; Otaki, Ryoji; Nishii, Kazuhiro; Kito, Takumi; Yao, Runhong; Uemura, Kenya; Izumi, Shin-ichi; Yamada, Kouji (Frontiers in Systems Neuroscience, 2022)
To execute intended movement, the brain directs attention, called body-specific attention, to the body to obtain information useful for movement. Body-specific attention to the hands has been examined but not that to the feet. We aimed to confirm the existence of body-specific attention to the hands and feet, and examine its relation to motor and sensory functions from a behavioral perspective. The study included two groups of 27 right-handed and right-footed healthy adults, respectively. Visual detection tasks were used to measure body-specific attention. We measured reaction times to visual stimuli on or off the self-body, and calculated the index of body-specific attention score to subtract the reaction time on self-body from that off one. Participants were classified into low and high attention groups based on each left and right body-specific attention index. For motor functions, Experiment 1 comprised hand grip strength and ball-rotation tasks for the hands and Experiment 2 comprised toe grip strength involved in postural control for the feet. For sensory functions, the tactile thresholds of the hands and feet were measured. The results showed that, in both hands, the reaction time to visual stimuli on the hand was significantly lesser than that off hand. In the foot, this facilitation effect was observed in the right foot but not the left, which showed correlation between body-specific attention and the normalized toe gripping force, suggesting that body-specific attention affected postural control. In the hand, the number of rotations of the ball was higher in the high than in the low attention group, regardless of the elaboration exercise difficulty or the left or right hand. However, this relation was not observed in the hand gripping task. Thus, body-specific attention to the hand is an important component of elaborate movements. The tactile threshold was higher in the high than in the low attention group, regardless of the side in hand and foot. The results suggested that more body-specific attention is directed to the limbs with lower tactile abilities, supporting the sensory information reaching the brain. Therefore, we suggested that body-specific attention regulates the sensory information to help motor control.